Influence of Barley Varieties and Nitrogen Levels on Chemical Properties of Soil under Saline Water Irrigation: Influence of barley varieties and nitrogen levels on soil - Amandeep Kaur; Satyavan (Journal of Soil Salinity and Water Quality, 2023)
Barley is now becoming more and more important as a commercial crop for industrial raw materials particularly with respect to malting and brewing. A field experiment was conducted at Hisar to study the effect of saline water irrigation on chemical properties of soil in four barley varieties (BH 902, BH 946, BH 885 and DWRB 101) at different nitrogen levels (0, 30, 60 and 90 kg ha-1). The results showed that after completion of two years of experimentation, soil pH decreased and its values varied from 8.06 to 8.15 among various treatments as compared to its initial value of 8.30. The EC values increased and the values ranged from 0.76 to 0.90 dS m-1 than its initial value of 0.33 dS m-1. The soil OC increased under different treatments (0.32 to 0.35%) as compared to its initial value (0.31%). Available N status of soil was increased from its initial status except under control in which it was slightly reduced. The available P (18.8 to 20.2 kg ha-1) and K status of soil (339.9 to 345.9 kg ha-1) was increased under various treatments from their initial status of 17.0 and 320.0 kg ha-1, respectively. Both 2-row barley varieties BH 885 and DWRB 101 exhibited significantly lower values of Na: K (0.63 to 0.64) at spike initiation stage as compared to 6-row varieties BH 902 and BH 946 (0.67 to 0.68), thus indicating better salt tolerance in 2-row barley varieties. All nitrogen levels significantly reduced Na: K ratio at spike initiation stage.